Saponins of Selected Triterpenoids as Potential Therapeutic Agents: A Review - Bildziukevich, Uladzimir; Wimmerová, Martina; Wimmer, Zdeněk (Pharmaceuticals (Basel, Switzerland), 2023)
Saponins represent important natural derivatives of plant triterpenoids that are secondary plant metabolites. Saponins, also named glycoconjugates, are available both as natural and synthetic products. This review is focused on saponins of the oleanane, ursane, and lupane types of triterpenoids that include several plant triterpenoids displaying various important pharmacological effects. Additional convenient structural modifications of naturally-occurring plant products often result in enhancing the pharmacological effects of the parent natural structures. This is an important objective for all semisynthetic modifications of the reviewed plant products, and it is included in this review paper as well. The period covered by this review (2019-2022) is relatively short, mainly due to the existence of previously published review papers in recent years.
Keywords: ursane; oleanane; saponin; glycoconjugate; lupane; pharmacological effects